Modelling dust polarization observations of molecular clouds through MHD simulations. Issue 4 (1st December 2017) - King, Patrick K; Fissel, Laura M; Chen, Che-Yu; Li, Zhi-Yun
Abstract: The BLASTPol observations of Vela C have provided the most detailed characterization of the polarization fraction p and dispersion in polarization angles S for a molecular cloud. We compare the observed distributions of p and S with those obtained in synthetic observations of simulations of molecular clouds, assuming homogeneous grain alignment. We find that the orientation of the mean magnetic field relative to the observer has a significant effect on the p and S distributions. These distributions for Vela C are most consistent with synthetic observations where the mean magnetic field is close to the line of sight. Our results point to apparent magnetic disorder in the Vela C molecular cloud, although it can be due to either an inclination effect (i.e. observing close to the mean field direction) or significant field tangling from strong turbulence/low magnetization. The joint correlations of p with column density and of S with column density for the synthetic observations generally agree poorly with the Vela C joint correlations, suggesting that understanding these correlations requires a more sophisticated treatment of grain alignment physics.